In-situ method to monitor surface reaction/oxidation at high temperature - Ani, Mohd Hanafi; Othman, Raihan; Ueda, Mitsutoshi; Kawamura, Kenichi; Maruyama, Toshio (2010)
The formation of external Cr2 O3 scale is important to obtain the oxidation resistance of Fe-Cr alloys at high temperatures. It is well known that the critical concentration of Cr to form protective external scale of Cr2 O3 in humid condition is higher than that in dry condition, and the criterion of this concentration is expressed as Wagner’s equation. To determine this concentration experimentally, a lot of mass gain data and metallographic surveys are required. An in-situ method of continuous monitoring of surface oxygen potential by oxygen concentration cell using stabilized zirconia has been developed and applied to the oxidation of Fe-Cr alloy in order to check the protectiveness of the scale. In our previous work, the oxygen chemical potential on growing oxide scales during high temperature oxidation of Fe, Ni, and Co were successfully measured. In this study, the surface oxygen potentials of Fe-0~17 wt% Cr alloys in Ar- 21%O2 gas as dry condition and Fe-10~22 wt% Cr alloys in Ar-20%O2 -20%H2 O gas as humid condition were measured at 1073 K up to 20 ks. In dry condition, the surface oxygen potentials of Fe with more than 10 wt% Cr alloys were close to the oxygen potential of atmosphere immediately after the heating period. It indicates that protective Cr2 O3 scale formed on these alloys at early stage of oxidation. However, the surface oxygen potentials of these same composition alloys were lower in humid condition than that in dry. By this method, the protectiveness of scales formed on Fe-Cr alloys can be evaluated in-situ in a few hours.